2016
DOI: 10.1167/iovs.16-19618
|View full text |Cite
|
Sign up to set email alerts
|

Different Ipsi- and Contralateral Glial Responses to Anti-VEGF and Triamcinolone Intravitreal Injections in Rats

Abstract: Citation: Di Pierdomenico J, García-Ayuso D, Jiménez-López M, AgudoBarriuso M, Vidal-Sanz M, VillegasPérez MP. Different ipsi-and contralateral glial responses to anti-VEGF and triamcinolone intravitreal injections in rats. Invest Ophthalmol Vis Sci. 2016;57:3533-3544. DOI:10.1167/iovs.16-19618 PURPOSE. To investigate the glial response of the rat retina to single or repeated intravitreal injections (IVI).METHODS. Albino Sprague-Dawley rats received one or three (one every 7 days) IVI of anti-rat VEGF (5 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 92 publications
1
31
1
Order By: Relevance
“…33 Indeed, it has been recently shown that macroglial cells hypertrophy across the whole retina after an apparently innocuous manipulation such as intravitreal injection of phosphate-buffered saline. 29 It was interesting to find that they also responded to topical administration of bromfenac, as evidenced by the significant increase of GFAP and vimentin and the decrease of CRALBP1 in extracts from intact retinas treated during 7 days with the NSAID. However, these changes reverted in ONC þ bromfenac retinas when compared to ONC alone, indicating, firstly, that the gliosis triggered by ONC is very strong and almost but not completely abolished by bromfenac, and, secondly, that treatment with this NSAID maintains retinal homeostasis after ONC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Indeed, it has been recently shown that macroglial cells hypertrophy across the whole retina after an apparently innocuous manipulation such as intravitreal injection of phosphate-buffered saline. 29 It was interesting to find that they also responded to topical administration of bromfenac, as evidenced by the significant increase of GFAP and vimentin and the decrease of CRALBP1 in extracts from intact retinas treated during 7 days with the NSAID. However, these changes reverted in ONC þ bromfenac retinas when compared to ONC alone, indicating, firstly, that the gliosis triggered by ONC is very strong and almost but not completely abolished by bromfenac, and, secondly, that treatment with this NSAID maintains retinal homeostasis after ONC.…”
Section: Discussionmentioning
confidence: 99%
“…21 Inflammation and edema are, as well, common responses to tissue damage or disease, as has been shown for the retina in animal models of glaucoma or optic nerve injury. [22][23][24][25][26][27][28] Macroglial retinal cells, astrocytes, and Müller cells readily respond to intravitreral injections, 29 injury, or disease. [30][31][32][33] A very well characterized model of retinal damage and degeneration is optic nerve axotomy in rodents.…”
mentioning
confidence: 99%
“…IVIs were performed only in the left eye following previously described methods that are standard in our laboratory. 39 Briefly, the injections were made through the supratemporal sclera using a Hamilton microsyringe (26G; Hamilton 701 N, Esslab, Benfleet, UK). Once the needle was visualized retrolenticularly, the liquid was injected and the needle was removed.…”
Section: Ivismentioning
confidence: 99%
“…Macroglial retinal cells: astrocytes and Müller cells, readily respond to intravitreral injections (Di Pierdomenico et al, 2016), injury or disease (Ramírez et al, 2010; Gallego et al, 2012; Rojas et al, 2014; de Hoz et al, 2016). Macroglial hypertrophy has been related to retinal stress or injury, and thus, gliosis has been used to assess the homeostatic state of the retina (Cuenca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%